2004
DOI: 10.1001/archopht.122.7.966
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Changes After Small-Incision Cataract Surgery in Patients WithDiabetes Mellitus

Abstract: To evaluate functional impairment in the corneal endothelium of eyes in patients with diabetes mellitus, after small-incision cataract surgery.Methods: Evaluation was performed in 93 eyes in patients with type 2 diabetes mellitus (diabetic group) and 93 eyes in patients without diabetic mellitus (nondiabetic group) who underwent cataract surgery. Using a topography system, the corneal thickness in the central area was measured before surgery and 1 day, 1 week, and 1 month after surgery. Corneal endothelial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
85
1
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 25 publications
9
85
1
7
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10]13,14 Majority of these reports showed that diabetic corneas were thicker when compared to non-diabetic healthy eyes. [5][6][7][14][15][16] Investigators demonstrated that endothelial pump dysfunction due to hyperglycaemia has been shown as the main mechanism of increased CCT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10]13,14 Majority of these reports showed that diabetic corneas were thicker when compared to non-diabetic healthy eyes. [5][6][7][14][15][16] Investigators demonstrated that endothelial pump dysfunction due to hyperglycaemia has been shown as the main mechanism of increased CCT.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators showed that high glucose levels lead to increased activity of aldose reductase. [1][2][3][4][5][6][7][8][9] As a result of increased activation of sorbitol-aldose reductase pathway; sorbitol is over produced and it is an osmotic agent which causes swelling of endothelial cells. Other unfavourable effect of DM on endothelial cells is reducing activity of Na + -K + ATPase pump.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Nitekim bizim olgularımızdan da DM'si olan 2 olguda %32 oranında EHS'de azalma görülürken, diğer 5 olgudaki ortalama azalmanın %19 düzeyinde olduğunu saptadık.…”
Section: Discussionunclassified
“…[71][72][73] This mechanically induced cell loss is greater in the diabetic cornea. 74,75 As such, greater effort and care should be utilized to minimize surgical trauma, by avoiding phaco power near the cornea and using viscoelastics generously to cushion the endothelium. Attention to wound construction and manipulation is also important in an attempt to minimize epithelial injury as well.…”
Section: Ocular Surgerymentioning
confidence: 99%